Perancangan Aktivasi Brand Untuk Sunny’s Time Beserta Media Promosinya - Maureen Tirza; Marina Wardaya (Jurnal Vicidi, 2022)
Many young children nowadays begin using electronic devices without parental supervision, which can lead to addiction and a lack of motor exercise. As a result of this phenomena, Sunny's Time is here to give educational games for children, with the goal of playing games that may encourage children to play and learn in a fun way enabling children's growth and development, along with helping minimize children's gadget hours. Sunny's Time expects recognition and trust from the target market as a new brand that has yet to be heard by the general public. The purpose of this research is to discover the best marketing and promotion approach to boosting brand awareness. The problem in this research is to figure out how to boost Sunny's Time brand awareness on social media by using the correct brand activation strategy and promotional platform. This design combines both qualitative and quantitative research approaches. To acquire the proper promotion data and conduct a design review, the qualitative method was used, which included interviews with three expert and three extreme users. The quantitative method is used to collect information on the most successful social media sites as well as webinars by assessing 121 respondents who meet the target market requirements, including parents who are female, between the ages of 29 and 35, and live in Indonesia. According to the findings of this research, the effective brand activation strategy for Sunny's Time is a parenting webinar including credible experts who will also introduce products and how to play. The Instagram app is the most effective social media platform for promoting Sunny's Time activation. Keywords: Brand Activation, Educational Games, Social Media